Emergency physicians accumulate more stress factors than other physicians–results from the French SESMAT study. Issue 5 (1st December 2010) - Estryn-Behar, M; Doppia, M-A; Guetarni, K; Fry, C; Machet, G; Pelloux, P; Aune, I; Muster, D; Lassaunière, J-M; Prudhomme, C
Abstract : Introduction: France is facing a shortage of available physicians due to a greying population and the lack of a proportional increase in the formation of doctors. Emergency physicians are the medical system's first line of defence. Methods: The authors prepared a comprehensive questionnaire using established scales measuring various aspects of working conditions, satisfaction and health of salaried physicians and pharmacists. It was made available online, and the two major associations of emergency physicians promoted its use. 3196 physicians filled out the questionnaire. Among them were 538 emergency physicians. To avoid bias, 1924 physicians were randomly selected from the total database to match the demographic characteristics of France's physician population: 42.5% women, 57.5% men, 8.2% <35 years old, 33.8% 35–44 years old, 34.5% 45–54 years old and 23.6% ≥55 years old. The distribution of physicians in the 23 administrative regions and by speciality was also precisely taken into account. This representative sample was used to compare subgroups of physicians by speciality. Results: The outcomes indicate that the intent to leave the profession (ITL) was quite prevalent across French physicians and even more so among emergency physicians (17.4% and 21.4% respectively), and burnout was highly prevalent (42.4% and 51.5%, respectively). Among the representative sample and among emergency physicians, work–family conflict (OR=4.47 and OR=6.14, respectively) and quality of teamwork (OR=2.21 and OR=5.44, respectively) were associated with burnout in a multivariate analysis, and these risk factors were more prevalent among emergency physicians than other types. A serious lack of quality of teamwork appears to be associated with a higher risk of ITL (OR=3.92 among the physicians in the representative sample and OR=4.35 among emergency physicians), and burnout doubled the risk of ITL in multivariate analysis. Conclusions: In order to prevent the premature departure of French doctors, it is important to improve work–family balance, working processes through collaboration, multidisciplinary teamwork and to develop team training approaches and ward design to facilitate teamwork.